2010
DOI: 10.1016/j.jterra.2009.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Development of hybrid electrical air-cushion tracked vehicle for swamp peat

Abstract: This study presents a developed hybrid electrical air-cushion tracked vehicle (HETAV) for the transportation operation of agricultural and industrial goods on the swamp peat terrain bearing capacity of 5 kN/m 2 . The vehicle's design parameters are optimized by using the developed mathematical models which are made based on the kinematics and dynamics behaviors of the vehicle. A set of sensors are used with this vehicle to activate the air-cushion system and battery pack recharging system. The vehicle's air-cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…8 and it is observed that the load distribution ratio affects the total power consumption significantly as total power consumption linearly increases with the increase of load distribution ratio. Based on previous researches [5,15], for the present IACTV, an optimal load distribution ratio of 0.2 was obtained which results in minimum power consumption of 3.5kW. Furthermore, the optimum total power consumption found from ANN was 3.42 kW which justified the above value.…”
Section: Effect Of Load Distribution On Total Power Consumptionsupporting
confidence: 69%
See 4 more Smart Citations
“…8 and it is observed that the load distribution ratio affects the total power consumption significantly as total power consumption linearly increases with the increase of load distribution ratio. Based on previous researches [5,15], for the present IACTV, an optimal load distribution ratio of 0.2 was obtained which results in minimum power consumption of 3.5kW. Furthermore, the optimum total power consumption found from ANN was 3.42 kW which justified the above value.…”
Section: Effect Of Load Distribution On Total Power Consumptionsupporting
confidence: 69%
“…1 [5]. The dry weight of the vehicle was considered as 2.43 kN and it was designed mainly for operating a maximum load of 3.43 kN including a 1.0 kN payload over the swamp peat terrain.…”
Section: Vehicle Descriptionmentioning
confidence: 99%
See 3 more Smart Citations